PENGARUH KEPEMIMPINAN KEPALA UPT PUSKESMAS TERHADAP KINERJA PEGAWAI PUSKESMAS CIAWI KECAMATAN CIAWI KABUPATEN BOGOR - Maulana, Irvan; Rahmawati, Rita; Salbiah, Euis (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2017)
The main objective of this research is to know the impact of leadership and employees performance at Ciawi Local Government Clinic of Bogor Municipality.Associative method is research method used to know the relationship or impact between two or more variables. The population of this research is 37 employees. To determine the number of minimum sample, Slovin formula is used. Based on the formula, 27 employees taken as sample. To analyze data, Weight Mean Score and Rank Spearman Correlation are used for hypothetical testing purpose. In this context, H0:Ï = 0, means that there is no positive correlation between leadership and employees performance, and Ha: Ï â 0, means that there is positive correlation between leadership and employees performance.The result of this research show that leadership function by Head of Local Government Clinic is in âpretty goodâ criteria with mean score of 2,916 (out of 5) and âpretty goodâ criteria in all of indicator in this variable. Meanwhile, the variable of employees performance is also categorized as âgoodâ criteria with mean score of 3,000 (out of 5). Futhermore, based on Rank Spearman analysis with significance test for n=27 and standar error of 10%, show that Rho 0,368 with âlowâ criteria. And the significance test t=2,042 > 1,70814, thus, conclusion can be taken that Ho is rejected and Ha is accepted. This mean that there is positive correlation between leadership and employees performance with coefficient of determination 13,5%. In the other words, the research conclusion is the influence of leadership efforts by head of Local Government Clinic is 13,5% and the remaining 86,5% is determined by other factors (epsilon).Â Key word : Leadership, Performance, employees